007.2 Can human papillomavirus (hpv) biomarkers help predict patterns of anal high-grade squamous intraepithelial lesion (hsil) detection in homosexual men?. (13th September 2015) - Jin, F; Poynten, IM; Cornall, AM; Phillips, Samuel; Roberts, J; Farnsworth, A; Hillman, RJ; Templeton, DJ; Garland, SM; Fairley, CK; Grulich, AE; Tabrizi, SN
Abstract : Background: Homosexual men suffer a disproportionally high burden of anal cancer for which persistent anal HSIL is the precursor. A range of biomarkers that potentially will enhance the performance of cytology-based HSIL screening are being investigated. We evaluated the role of biomarkers in predicting the development and clearance of anal HSIL. Methods: The Study of the Prevention of Anal Cancer is a Sydney-based three-year prospective study of anal HPV infection in homosexual men aged ≥35 years. At each visit all men undergo liquid-based Pap test (ThinPrep©), followed by high-resolution anoscopy-guided biopsy. In this analysis, residual baseline PreservCyt samples underwent HPV E6/E7 mRNA testing (NucliSENS EasyQ, BioMerieux) and p16/Ki67 dual staining (CINtec PLUS, Roche). Anal HSIL was defined as having either anal intraepithelial neoplasia grade 2/3 on histology and/or HSIL on cytology. Results: By February 2015, 302 men had completed one-year of follow-up, with a median age of 49.5 years and around a quarter (27.8%) were HIV-positive. The prevalence of anal HSIL at baseline was 37.4%. Among 179 men who did not have HSIL at baseline, 29 (16.2%) developed HSIL at one year. In those who tested positive to HPV16/18 E6/E7 mRNA or p16/Ki67, 43.3% and 38.5% developed incident HSIL respectively, compared with 11.8% and 8.7% in those who tested negative to that biomarker (Risk Ratio (RR): 3.68, 95% CI 1.99–6.82 and 4.42, 95% CI 1.54–12.70, respectively). Among men with prevalent HSIL, 44 (38.9%) had no HSIL detected after one year. Those negative for HPV16/18 E6/E7 mRNA were twice as likely to have no HSIL at one-year (53.5% vs 28.1%, RR: 1.90, 95% CI 1.18–3.08). Conclusion: Anal HSIL is a very dynamic condition, with high incidence and high rates of non-detection at subsequent visits. Biomarkers of HPV activity can help predict incidence and subsequent non-detection, and thus potentially allow more targeted therapies. Disclosure of interest statement: AEG has received honoraria and research funding from CSL Biotherapies, honoraria and travel funding from Merck, and sits on the Australian advisory board for the Gardasil HPV vaccine. CKF has received honoraria, travel funding and research funding from CSL and Merck, sits on the Australian advisory board for the Gardasil HPV vaccine, and owns shares in CSL Biotherapies. SMG has had grant support from CSL Bio and GlaxoSmithKline, and lecture fees from Merck, GlaxoSmithKline and Sanofi Pasteur; in addition, has received funding through her institution to conduct HPV vaccine studies for MSD and GlaxoSmithKline and is a member of the Merck Global Advisory Board as well as the Merck Scientific Advisory Committee for HPV. RJH has received support from CSL Biotherapies and MSD. All other authors declare that they have no conflicts of interest.